Sertula florae colombiae, vi (1962)
Melastomataceae Novae / Meriania peltata L. Uribe, sp. nov. / Meriania versicolor L. Uribe, sr. nov. / Miconia eremita L. Uribe, sp. nov. / Ernestia adenotricha L. Uribe, sp. nov.